2021
DOI: 10.3390/atmos12081072
|View full text |Cite
|
Sign up to set email alerts
|

30 Years of Air Quality Trends in Japan

Abstract: The aim of this paper is to obtain information that will contribute to measures and research needed to further improve the air quality in Japan. The trends and characteristics of air pollutant concentrations, especially PM2.5, ozone, and related substances, over the past 30 years, are analyzed, and the relationships between concentrations and emissions are discussed quantitatively. We found that PM2.5 mass concentrations have decreased, with the largest reduction in elemental carbon (EC) as the PM2.5 component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 9 publications
1
19
0
Order By: Relevance
“…However, the NO 2 level increased by ~ 13% year −1 from 2013 to 2015. As per the observation of Ito et al (2021), a significant reduction in (~ 75%) SO 2 concentrations has been detected in Japan over 30 years . Jang et al (2017) observed an increasing trend of SO 2 levels in the rural and commercial sites of Busan, South Korea, throughout the period from 2005 to 2014 due to local emissions from shipping industries, while NO 2 levels remain constant.…”
Section: The Annual Trend Of So 2 and Nosupporting
confidence: 56%
“…However, the NO 2 level increased by ~ 13% year −1 from 2013 to 2015. As per the observation of Ito et al (2021), a significant reduction in (~ 75%) SO 2 concentrations has been detected in Japan over 30 years . Jang et al (2017) observed an increasing trend of SO 2 levels in the rural and commercial sites of Busan, South Korea, throughout the period from 2005 to 2014 due to local emissions from shipping industries, while NO 2 levels remain constant.…”
Section: The Annual Trend Of So 2 and Nosupporting
confidence: 56%
“…The reduction of NO 2 in 2018-2019 could be due to the decommissioning of the Ainoura Power Station, a crude oil-fired power www.nature.com/scientificreports/ plant. The more gradual decrease of NO 2 during the study period, as indicated by the trend and forecast analysis, can be attributed, among other factors, to the stricter vehicle emission regulations implemented 22 and also the regulation of emissions from stationary sources such as fossil fuel powerplants, electric and industrial boilers.…”
Section: Discussionmentioning
confidence: 89%
“…Air pollution trends differ by pollutant and by country. In Japan and Thailand, decreasing trends of CO, NOx, SO2 and PM were found, whereas O3 was increasing (Aziz et al, 2016;Ito, et al, 2021). In Malaysia, CO and SO2 had decreasing trends, and O3 an increasing trend (Mohtar et al, 2018).…”
Section: Introductionmentioning
confidence: 99%